Market-based Task Allocation for Dynamic Information Processing Environments - WELLMAN, Michael P. (Institutional Knowledge at Singapore Management University, 2003)
Flexible and large-scale information processing across enterprises entails dynamic and decentralized control of workflow through adaptive allocation of knowledge and processing resources. Markets comprise a well-understood class of mechanisms for decentralized resource allocation, where agents interacting through a price system direct resources toward their most valued uses as indicated by these prices. The information-processing domain presents several challenges for market-based approaches, including (1) representing knowledge-intensive tasks and capabilities, (2) propagating price signals across multiple levels of information processing, (3) handling dynamic task arrival and changing priorities, and (4) accommodating the increasing-returns and public-good characteristics of information products. A market gaming environment provides a methodology for testing alternative market structures and agent strategies, and evaluating proposed solutions in a realistic decentralized manner.